Analysis of willingness to pay visitors to ecotourism: The case of the Pindul Cave, Yogyakarta - Rozaq, Yusya Fatnan Subkhi Miftakhur (Economics, Finance, and Business Review, 2025)
This research aims to identify factors that influence willingness to pay in order to improve environmental quality at the Pindul Cave tourist attraction, Gunungkidul Regency, Yogyakarta. This study uses primary data with 95 respondents selected through a purposive sampling technique. The contingent valuation method (CVM) is employed to analyze the willingness to pay. The results show that 81.05% of visitors are willing to improve the environmental quality of the Pindul Cave tourist. According to the logistic regression, the Education level, recreation costs, and frequency of visits have a positive influence on willingness to pay, but the number of dependents has a negative influence on willingness to pay. However, income and age do not influence the willingness to pay to improve the environmental quality of the Pindul Cave tourists. This research recommends that managers of Pindul Cave tourists carry out intensive promotions, add facilities for visitors such as parking areas, clean toilets, rubbish boxes, and food and souvenir zones, and introduce the natural and cultural potential that exists at tourist attractions.